The effect of international trade and foreign direct investment towards exchange rate volatility in the ASEAN countries / Noorhayati Abas - Abas, Noorhayati (2019)
Exchange rate has a vital role in the country's level of trade, which in turn is very critical in a free market economy. This study aims to study the relationships between the effect of International Trade and Foreign Direct Investment towards Exchange rates Volatility by using the evidence from 10 Asean Countries. The variables that used for this study are Exchange rate Volatility, International Trade and Foreign Direct Investment. This study pooled by OLS and proceeds with Robust Standard Error due to the existence of Heteroskedasticity. After conducting Robust Standard Error, the variables that show negative impact is Foreign Direct Investment and positive impact is International trade towards Exchange rates Volatility. However, there is no variables that have significant relationship towards Exchange rates Volatility.